2017
DOI: 10.1057/s41267-017-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Explicit versus implicit country stereotypes as predictors of product preferences: Insights from the stereotype content model

Abstract: Drawing on the Stereotype Content Model (SCM), we investigate the impact of both explicit and implicit country stereotypes on consumer preferences. In Study 1, we show that the competence dimension of the SCM (measured both explicitly and implicitly) drives purchase intention by positively influencing brand affect. In Study 2, we disentangle further the role of explicit and implicit stereotypes and show that explicit judgments of country competence are better predictors of deliberate consumer choices, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 57 publications
(87 reference statements)
5
102
0
Order By: Relevance
“…Many consumers use these stereotypical associations to assess products (Yasin et al, 2007). Country of brand origin is known to originate associations with a specific source country in consumers' minds (Aaker, 1991;Keller, 1993), regardless of where the product is actually produced (Diamantopoulos, Florack, Halkias, & Palcu, 2017). Previous studies have indicated that country of origin signals the value of a brand, serves a cue for product quality, helps to reduces consumer perceived risk and facilitates purchase decision (e.g.…”
Section: Country Of Brand Originmentioning
confidence: 99%
“…Many consumers use these stereotypical associations to assess products (Yasin et al, 2007). Country of brand origin is known to originate associations with a specific source country in consumers' minds (Aaker, 1991;Keller, 1993), regardless of where the product is actually produced (Diamantopoulos, Florack, Halkias, & Palcu, 2017). Previous studies have indicated that country of origin signals the value of a brand, serves a cue for product quality, helps to reduces consumer perceived risk and facilitates purchase decision (e.g.…”
Section: Country Of Brand Originmentioning
confidence: 99%
“…Concerning the outcomes of brand emotions, some scholars have demonstrated that brand emotion could significantly influence a customer's behavior towards a product. For example, brand emotion influences purchase intention [20], brand equity [21], and brand loyalty [22,23]. Brand emotion also strongly influences brand extension [24].…”
Section: H2: Alternative Attractiveness Positively Influences Negativmentioning
confidence: 99%
“…In empirical work, schemata have been used as theoretical vehicles to explain (1) how congruence between consumer culture ad imagery and brand image affects the effectiveness of foreign brand communications , (2) how consumers form stereotypes (i.e. collectively shared schemata) about brands and products based on their globalness/localness (Davvetas and Halkias 2019) or country of origin (Diamantopoulos et al 2017), and (3) how home country-brand schema congruence enhances brand evaluations (Magnusson, Westjohn, and Sirianni 2018).…”
Section: Direction Of Global Brand Halo Effects: the Role Of Consumermentioning
confidence: 99%